Soil puddling for reducing seepage - Smith, Stephen W., author; Hart, William E., advisor; Walker, Wynn R., committee member; Ward, Robert C., committee member; Shaner, Willis W., committee member (Colorado State University. Libraries, 1975)
This thesis is a report of laboratory and field studies designed to determine the potential of soil puddling for reducing seepage in irrigation distribution systems. Laboratory studies were conducted under ideal conditions of thorough puddling, a screened soil, constant head, and nearly constant temperature. Field studies were conducted under less controlled but more realistic conditions. A 26-foot, polyethylene covered, rectangular channel was constructed at three field sites, and seepage was monitored before and after puddling the channel invert. Hand and mechanical puddling methods were employed. Labor input is less and the effectiveness of the puddled layer greater with mechanical puddling. Results indicate that soil puddling has potential for reducing seepage, particularly when the entire channel perimeter can be puddled. This method can be labor intensive and adaptable to the situation found in many developing countries.
Keywords: Seepage; Puddling (Horticulture); Irrigation canals and flumes -- Linings; Irrigation -- Developing countries